Anais Do XXVI Simpósio Brasileiro De Informática Na Educação (SBIE 2015) 2015
DOI: 10.5753/cbie.sbie.2015.627
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso de realidade aumentada e gamificação para o treinamento de habilidades em laparoscopia

Abstract: Abstract. Minimally Invasive Surgeries (MIS) require learning and training of non-conventional skills of surgeons (e.g., hand-eye coordination, manual dexterity and precision). In laparoscopic box-trainers, these skills can be practiced with simple navigation and coordination activities. In this paper, we propose to extend laparoscopic box-trainers with Augmented Reality (AR) and Gamification techniques. Our proposal introduces an extra camera, and uses tracking algorithms in order to monitor movements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Some of the selected studies reported the use of innovative technologies, such as augmented reality and gamification, for skills training in minimally invasive surgery. These tools can be useful to improve the efficiency and quality of surgeon training (SILVA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the selected studies reported the use of innovative technologies, such as augmented reality and gamification, for skills training in minimally invasive surgery. These tools can be useful to improve the efficiency and quality of surgeon training (SILVA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…To strengthen the use of this approach, Silva et al (2015) propose the association of the technique with other technological resources. In their study, the authors looked at the use of augmented reality and gamification for laparoscopic skills training, underscoring how the use of these technologies can improve the efficiency and quality of surgeon training.…”
Section: Mohr Et Al (1998) Present the Technique Of Minimally Invasiv...mentioning
confidence: 99%
See 1 more Smart Citation